Depression and Pain Interference Correlate With Physical Function in Patients Recovering From Hand Surgery. (November 2019) - Crijns, Tom J.; Bernstein, David N.; Ring, David; Gonzalez, Ronald M.; Wilbur, Danielle M.; Hammert, Warren C.
Background: Patient-reported outcome measures vary more than expected based on underlying pathology, in part due to the substantial influence of mood and coping strategies.Methods: This study addressed the primary null hypothesis that the Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function score 1 month (range, 3-8 weeks) after hand surgery is not associated with PROMIS Depression and PROMIS Pain Interference scores prior to surgery, accounting for other factors. Using an institution-wide database of routinely collected patient-reported outcomes, we identified adult patients who underwent wrist ganglion excision, trapeziometacarpal arthroplasty, hand ganglion excision, trigger digit, De Quervain, and carpal tunnel release. Measures collected included the PROMIS Physical Function Computerized Adaptive Test (CAT), PROMIS Pain Interference CAT, and PROMIS Depression CAT. We sought factors associated with postsurgical PROMIS Physical Function scores and change between preoperative and postoperative score using multivariable linear regression, accounting for age, sex, surgery type, provider, and time from surgery to postsurgical measurement.Results: Higher postoperative PROMIS Physical Function score was independently associated with lower PROMIS Pain Interference scores, lower PROMIS Depression scores, younger age, and treatment by provider team 3. Greater change in PROMIS Physical Function score was independently associated with greater PROMIS Pain Interference scores, greater time from surgery, and treatment by provider team 3.Conclusions: Mood and effective coping strategies affect the level of symptoms and limitations during recovery from hand surgery and represent important treatment opportunities for enhancing recovery.